Ambient Learning Environment: An Integrative Review of Students' Learning Experience and Engagement - Prelatha, Renukha; Choo, Koo Ah; Wafa, Syarifah Nurleyana (Journal of Cultural Analysis and Social Change, 2026)
In recent years, many educational institutions have sought to enhance student engagement through the improvement of learning spaces, leading to a growing interest in learning space design. However, while various studies have explored technological and environmental factors that shape the learning experience, the specific influence of lighting and spatial design on student learning remains not fully understood. This study examines how ambient learning environment engages student learning by synthesizing research conducted from 2021-2025. It explores how ambient learning environments influence students' experiences, with a specific focus on lighting and spatial elements. This integrative review analyzed ten peer-reviewed articles that were systematically selected based on established inclusion and exclusion criteria, and the findings were synthesized through thematic analysis. The findings show that five major themes of experience emerged, namely lighting effects, spatial design, motivation & engagement, co-design & flexibility, and learning outcomes & satisfaction. The findings suggest that a balance of natural and artificial lighting positively influences students’ psychological state and cognitive abilities. Finally, this study proposes a framework for a multimedia-enhanced ambient learning environment, grounded in the principles of Embodied Cognition Theory. The framework consolidates the key findings of this review and illustrates how embodiment concepts underpin its structure. It is anticipated that this learning framework will enhance students’ experiences, engagement, and creativity, ultimately contributing to improved academic performance.